2011
DOI: 10.1124/jpet.110.172809
|View full text |Cite
|
Sign up to set email alerts
|

Tipifarnib-Induced Apoptosis in Acute Myeloid Leukemia and Multiple Myeloma Cells Depends on Ca2+Influx through Plasma Membrane Ca2+Channels

Abstract: A major contributing factor to the high mortality rate associated with acute myeloid leukemia and multiple myeloma is the development of resistance to chemotherapy. We have shown that the combination of tipifarnib, a nonpeptidomimetic farnesyltransferase inhibitor (FTI), with bortezomib, a proteosome inhibitor, promotes synergistic death and overcomes de novo drug resistance in acute myeloid leukemia cell lines. Experiments were undertaken to identify the molecular mechanisms by which tipifarnib produces cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 38 publications
1
31
0
1
Order By: Relevance
“…The increase in cytosolic calcium occurred 4-8 h following glucopsychosine treatment, which is consistent with other studies reporting slower increases in cytosolic calcium when the calcium originates from the extracellular space [79,80]. Increased cytosolic calcium resulted in calpain activation.…”
Section: Discussionsupporting
confidence: 91%
“…The increase in cytosolic calcium occurred 4-8 h following glucopsychosine treatment, which is consistent with other studies reporting slower increases in cytosolic calcium when the calcium originates from the extracellular space [79,80]. Increased cytosolic calcium resulted in calpain activation.…”
Section: Discussionsupporting
confidence: 91%
“…The authors reported higher Orai3 expression in Tipifarnib-sensitive myeloid leukemia cells in comparison to Tipifarnib-insensitive leukemia cells. Further, using pharmacological tools, Yanamandra et al (113) showed that Orai3 contributes to Tipifarnib-induced apoptosis in myeloid leukemia cell lines. In contrast to a large number of studies, Peng et al (81) reported that increased STIM1 expression and SOCE negatively regulate benign cancerous conditions of tuberous sclerosis complex.…”
Section: Other Cancersmentioning
confidence: 99%
“…They examined Orai3 mRNA levels in these cell lines and reported that tipifarnib-sensitive cells express higher levels of Orai3 mRNA compared with tipifarnib-resistant cells, suggesting that the difference in mRNA expression might explain Orai3 involvement in these cells. 74 Although the study by Yanamandra et al reported some interesting observations, …”
Section: Orai3 In Leukemiamentioning
confidence: 61%
“…This group reported that some leukemic cell lines possess a tipifarnibactivated Ca 2+ influx pathway with a pharmacological profile similar to that of SOCE mediated by Orai3 in ER + breast cancer cells; tipifarnib-induced Ca 2+ influx is potentiated by 2-APB and blocked by lanthanides. 74 These authors correlated the extent of Ca 2+ entry with cell death and found that application of tipifarnib alone resulted in apoptosis; co-application of 2-APB increased apoptosis whereas co-application of lanthanides decreased tipifarnib-induced apoptosis. They examined Orai3 mRNA levels in these cell lines and reported that tipifarnib-sensitive cells express higher levels of Orai3 mRNA compared with tipifarnib-resistant cells, suggesting that the difference in mRNA expression might explain Orai3 involvement in these cells.…”
Section: Orai3 In Leukemiamentioning
confidence: 99%
See 1 more Smart Citation